Attitudes to feed fermentation for aflatoxin management in maize in Kenya: Investigating aflatoxin reduction by yeast-fermentation - Hayo, E. (2018)
Aflatoxins are toxins produced by certain strains of fungi belonging to the species Aspergillus flavus and Aspergillus parasiticus during infection in the field, post-harvest, storage and processing. Aflatoxins are found especially in maize and also carry over into milk when contaminated feeds are fed to dairy cows. Feed fermentation could possibly be used to reduce the level of aflatoxin in animal feed. The project investigates, with survey interviews, if Kenyan farmers are willing to use novel fermentation methods to reduce the level of aflatoxin. The project will give better understanding of the farmers’ opinions and situation. The survey part involved 184 smallholder farmers in urban and peri-urban areas in Kasarani and Kisumu.